Monitoring the agri-food system in Myanmar: Food vendors - September 2021 survey round - Myanmar Agriculture Support Activity (International Food Policy Research Institute, 2021)
Most food retail prices in September 2021 were found to be substantially higher than in September 2020. Retail prices of the cheapest variety of rice–by far the most important staple in Myanmar–have risen by 8 percent, on average. The relatively more expensive but widely locally consumed rice (pawsan) increased by 17 percent. Relative to September 2020, national-level food price inflation in September 2021 stood at 11 percent. Inflation was highest in the Hills and Mountains areas (15 percent). Households in the poorest quintile were affected by food price inflation more than those in the richest while rural areas (12 percent) were exposed to almost twice the level of food inflation compared to urban areas (6 percent). Food availability is seemingly not a challenge at the national level in September 2021. Food vendors report that availability of most commodities is comparable to the same period in a normal year. However, there are increasing trade frictions with higher transportation costs and more frequent mobility issues due to lockdowns and insecurity problems. COVID-19 prevention measures were widely practiced by market vendors in 2020. While they had been abandoned by a substantial share of vendors surveyed in the middle of the year, these prevention measures were again widely adhered to in September 2021.